2014
DOI: 10.1177/0149206314551962
|View full text |Cite
|
Sign up to set email alerts
|

The Prowess and Pitfalls of Bayesian Structural Equation Modeling

Abstract: Muthén and Asparouhov introduced an approach for conducting Bayesian inference in the context of structural equation models that they termed Bayesian structural equation modeling (BSEM). In this article, we provide an overview of the BSEM technique, illustrate how this technique relates to confirmatory and exploratory factor analysis, and highlight several key problems with using the BSEM approach as it is currently advocated. Utilizing data from a large-scale study of entrepreneurial self-efficacy, we develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 82 publications
(167 reference statements)
1
64
0
Order By: Relevance
“…Given there is no “right” approach for model selection in moderated mediation, we echo Cudeck and Henly's () and Stromeyer et al. 's () recommendations for scholars to articulate the criteria utilized when making model selection decisions. Beyond selecting a mathematical model from a set of alternatives, scholars face the challenge of justifying the chosen structure vis‐à‐vis a universe of potential alternatives.…”
Section: Limitationsmentioning
confidence: 56%
“…Given there is no “right” approach for model selection in moderated mediation, we echo Cudeck and Henly's () and Stromeyer et al. 's () recommendations for scholars to articulate the criteria utilized when making model selection decisions. Beyond selecting a mathematical model from a set of alternatives, scholars face the challenge of justifying the chosen structure vis‐à‐vis a universe of potential alternatives.…”
Section: Limitationsmentioning
confidence: 56%
“…Because of this, Bayesian estimation may permit an otherwise nonidentified model to be identified. The practice of estimating all correlated residuals is currently a topic of debate with some suggesting it should be avoided (Stromeyer, Miller, Sriramachandramurthy, & DeMartino, ) and others contending that it better clarifies an instrument's structure (Muthén & Asparouhov, ). Stromeyer et al.…”
Section: Factor Structure Of the Das–iimentioning
confidence: 99%
“…() criticized the use of simultaneous estimation of small but informative correlated error terms; however, Asparouhov, Muthén, and Morin () suggested that Stromeyer et al. () may have misapprehended the approach and provided additional guidelines for the use of small variance correlated residuals. Asparouhov et al.…”
Section: Factor Structure Of the Das–iimentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors of the recent papers refer to a need for fully automated software that fits latent variable models via MCMC, with Mplus (Muthén & Muthén, 1998) providing SEM functionality and BUGS (Lunn et al, 2012), JAGS (Plummer, 2003), and Stan (Stan Development Team, 2014) providing general functionality. This automation has the reward of easily estimating complex models coupled with the risk of estimating inappropriate models or drawing inappropriate conclusions (also see MacCallum, Edwards, & Cai, 2012;Steiger, 2001;Stromeyer, Miller, Sriramachandramurthy, & DeMartino, 2014).…”
mentioning
confidence: 99%